GE_GERICHTE A/2453/2024 vom 22. Juli 2024 - GE Cour de justice (2024)
MESURE DE CONTRAINTE(DROIT DES ÉTRANGERS);DÉTENTION AUX FINS D'EXPULSION | LEI.75.al1.leth; LEI.76.al1.letb; LEI.76.al1.letb.ch3; LEI.76.al1.letb.ch4